Does Occupational Self-Competence Perception Relate to Functional Outcomes After Total Knee Arthroplasty? - Yılmaz, Güleser Güney; AKEL, BURCU SEMİN; SAİTOĞLU, YELİZ SEVİMLİ; Akı, Esra (Hayat Sağlık ve Sosyal Hizmetler Vakfı, 2024)
Aim: The study investigates the effect of occupational self-perception level on the functional status in the early period after total knee arthroplasty (TKA). Methods: Occupational Self Assessment (OSA), Canadian Occupational Performance Measure (COPM), Knee Injury and Osteoarthritis Outcome Score (KOOS), and Timed Up and Go Test (TUG) tests were administered before and at the 3rd and 6th week after surgery. Changes in COPM, KOOS, and TUG tests were analyzed using Friedman test. The relationship of OSA was examined using the Pearson correlation test. Results: Self-perception score was statistically in relation to TUG (r =- 0.600; p = 0.001). It was not significantly related with other assessment scores (p>0.05). Conclusion: Occupational self-competence perception of individuals affect their actual performance levels therefore; high occupational self-perception level may affect the recovery positively.
Total Diz Artroplastisi Sonrası Aktivite Öz Yeterlik Algısının Fonksiyonel Sonuçlarla İlişkisi Var Mı?
Keywords: Ctivities of Daily Living; Recovery of Function; Total Knee Replacement